Mitochondrial Fission Is Required for Blue Light-Induced Apoptosis and Mitophagy in Retinal Neuronal R28 Cells - Li, Jia-Yu; Zhang, Kun; Xu, Dan; Zhou, Wen-Tian; Fang, Wen-Qing; Wan, Yu-Ying; Yan, Dan-Dan; Guo, Miao-Yu; Tao, Jin-Xin; Zhou, Wen-Chuan; Yang, Fan; Jiang, Li-Ping; et al. (Frontiers in Molecular Neuroscience, 2018)
Light emitting diodes (LEDs) have been widely used to provide illumination for its low energy and high brightness. However, the spectrum of LEDs contains an intense blue light component, which is phototoxic to retina. Recently, it has been reported that blue light may directly impinge on mitochondrial functions in retinal ganglion cells (RGCs). Mitochondria are high dynamic organelles with frequent fission and fusion events. The aim of our study was to elucidate the role of mitochondrial dynamics in blue light-induced damage in retinal neuronal R28 cells. We found that exposure to blue light (450nm, 1000 Lux) for up to 12 h significantly up-regulated the expression of mitochondrial fission protein Drp1, whereas down-regulated the expression of mitochondrial fusion protein Mfn2 in cells. Mitochondrial fission was simultaneously stimulated by blue light irradiation. In addition, exposure to blue light increased reactive oxygen species (ROS) production, disrupted mitochondrial membrane potential (MMP), and induced apoptosis in R28 cells. Notably, Drp1 inhibitor Mdivi-1and Drp1 RNAi not only attenuated blue light-induced mitochondrial fission, but also alleviated blue light-induced ROS production, MMP disruption and apoptosis in cells. Compared with Mdivi-1 and Drp1 RNAi, the antioxidant N-Acetyl-L-cysteine (NAC) slightly inhibited mitochondrial fission, whereas significantly alleviated apoptosis after blue light. Moreover, we examined the markers of mitophagy which is responsible for clearance of the dysfunctional mitochondria. It was found that blue light stimulated the conversion of LC3B-I to LC3B-II and expression of Pink1 in R28 cells. Mdivi-1 or Drp1 RNAi efficiently inhibited blue light-induced expression of Pink1 and co-localization of LC3 on mitochondria. Thus, our data suggest that mitochondrial fission is required for blue light-induced mitochondrial dysfunctions and apoptosis in RGCs.